Effect of Protein Supplementation on Orthostatic Hypotension in Older Adult Patients with Heart Failure - Gohar Azhar; Amanda K. Pangle; Karen Coker; Shakshi Sharma; Jeanne Y. Wei (Geriatrics)
Purpose: Heart failure (HF) impairs physical performance and increases the incidence of orthostatic hypotension (OH). Individuals with OH have a higher risk of falls, which are a major source of morbidity and mortality in older adults. Dietary protein supplementation can improve physical performance in healthy older adult individuals; however, its effect on OH in older adult patients with HF is unknown. Methods: Twenty-one older adult patients with mild-to-moderate HF were randomized to placebo or protein supplementation. Dietary protein was supplemented with whey protein so the total protein intake for each participant was 1.2 g/kg bodyweight/day, plus 1 g/day of the amino acid l-carnitine for 16 weeks. Susceptibility to OH was assessed using a head-up tilt test, blood markers, and a functional test (6 min walk) at baseline and 16 weeks. Results: There were no differences in tilt test responses or 6 min walk test (6MWT) distances. The protein-supplement group had a significant increase in 6MWT pulse pressures post-walk after 16 weeks of treatment as compared to placebo. However, the tachycardia observed at baseline after 6MWT in the protein group was not seen at the end of the study. There was also a trend towards lower levels of brain naturetic peptide (proBNP) in the protein group vs. placebo at 16 weeks. Conclusions: The improved pulse-pressure response to exertion and positive trends in proBNP in this pilot study suggest that dietary supplementation may improve cardiovascular function and general health in individuals with HF and that larger future studies are justifiable.